Integration of Nutrients, Immune Response, and Metabolism in Health and Disease - Rizzo, Toni (MD Conference Express, 2014)
The pandemic of metabolic disease caused by the increase in obesity is the greatest current threat to human health. At this time, 1.2 billion people worldwide are overweight or obese, and 400 million have been diagnosed with diabetes. This article discusses the integration of nutrients, immune response, and metabolism in health and disease.